THE EFFECTIVENESS OF RECIPROCAL TEACHING STRATEGY TO TEACH READING COMPREHENSION IN NARRATIVE TEXT TO THE ELEVENTH-GRADE STUDENTS OF SMAN 1 KUTOREJO - Sonya Brinda; Cindi Eka Whardatul Jannah (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2021)
Reading had become one of the essential English skills which should be mastered by students in their English learning. Furthermore, in reading activity, students could enrich their vocabulary, practice their pronunciation which also useful in speaking, writing, even listening skills. However, sometimes students could face some problems which they have experienced when reading those texts, even if they were encountering with reading texts at school. Thus, students needed the teachers’ guidances in their English learning because most of them could be classified as the beginner stage. This research was aimed to measure and investigate the effectiveness of Reciprocal Teaching strategy to teach reading comprehension in narrative text to the eleventh-grade students of SMAN 1 Kutorejo. The researcher had used quasi-experimental research which picked two classes to become the samples from eleventh-grade classes in SMAN 1 Kutorejo by using the purposive sampling technique. Those classes were chosen randomly as the experiment class. One class which would be taught by using Reciprocal Teaching strategy was XI-IPA 1, while the other class, XI-IPA 5 would be taught by using Non Reciprocal Teaching strategy. Furthermore, the researcher had prepared the post-test which contained 50 questions with multiple choice about narrative text reading comprehension for both eleventh-grade classes to collect the data. The data which had been gotten from the post-test were analyzed by using the statistical technique with an independent t-test formula that would show the differences between both classes that have different treatments.